Addressing forest Degradation: Role of Ecosystem Services - Gera, Mohit (Indian Forester, 2017)
Forest ecosystem services are the consumptive benefits from forests like timber, non-timber forest products, genetic resources and fresh water along with non-consumptive benefits such as ecotourism. They also include functional benefits like carbon sequestration and storage, hydrological services, watershed protection, biological control and pollination. Despite high importance attached to forest ecosystems for providing goods and services, the communities and private individuals often lack incentives to protect and conserve forests resulting in their degradation. Ironically, India’s forests also face a similar situation wherein despite gradually increasing forest and tree cover, the quality of forests is not of the desired level as evident from poor natural regeneration, unregulated grazing, and high incidences of fire, illicit felling, girdling and lopping. Recognition to the forest ecosystem services and their mainstreaming in policy and action for incentivizing the providers of these services, viz., communities, individuals and departments is seen world over as a solution to tackle the problem of forest degradation. The paper taking clues from other countries articulate the need for a policy in line of ’Beneficiary Pays’ principle wherein the providers of forest ecosystem services are duly rewarded so as to ensure that forests are not only saved from further degradation but also improved and conserved for posterity.